Calcium lignosulfonate improves proliferation of recalcitrant indica rice callus via modulation of auxin biosynthesis and enhancement of nutrient absorption - Wan Abdullah, Wan Muhamad Asrul Nizam; Tane, Ngai-Paing; Low, Lee Yoon; Loh, Jiun Yan; Wee, Chien Yeong; Md Taib, Azney Zuhaily; Ong Abdullah, Janna; Lai, Ok Song (Elsevier, 2021)
Lignosulfonate (LS) is a commonly used to promote plant growth. However, the underlying growth promoting responses of LS in plant remain unknown. Therefore, this study was undertaken to elucidate the underlying growth promoting mechanisms of LS, specifically calcium lignosulfonate (CaLS). Addition of 100 mg/L CaLS in phytohormone-free media enhanced recalcitrant indica rice cv. MR219 callus proliferation rate and adventitious root formation. Both, auxin related genes (OsNIT1, OsTAA1 and OsYUC1) and tryptophan biosynthesis proteins were upregulated in CaLS-treated calli which corroborated with increased of endogenous auxin content. Moreover, increment of OsWOX11 gene on CaLS-treated calli implying that the raised of endogenous auxin was utilized as a cue to enhance adventitious root development. Besides, CaLS-treated calli showed higher nutrient ions content with major increment in calcium and potassium ions. Consistently, increased of potassium protein kinases genes (OsAKT1, OsHAK5, OsCBL, OsCIPK23 and OsCamk1) were also recorded. In CaLS treated calli, the significant increase of calcium ion was observed starting from week one while potassium ion only recorded significant increase on week two onwards, suggesting that increment of potassium ion might be dependent on the calcium ion content in the plant cell. Additionally, reduced callus blackening was also coherent with downregulation of ROS scavenging protein and reduced H2O2 content in CaLS-treated calli suggesting the role of CaLS in mediating cellular homeostasis via prevention of oxidative burst in the cell. Taken together, CaLS successfully improved MR219 callus proliferation and root formation by increasing endogenous auxin synthesis, enhancing nutrients uptake and regulating cellular homeostasis.